Health-related life cycle risks and public insurance - Daniel Kemptner (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper proposes a dynamic life cycle model of health risks, employment, early retirement, and wealth accumulation in order to analyze the health-related risks of consumption and old age poverty. In particular, the model includes a health process, the interaction between health and employment risks, and an explicit modeling of the German public insurance schemes. I rely on a dynamic programming discrete choice framework and estimate the model using data from the German Socio-Economic Panel. I quantify the health-related life cycle risks by simulating scenarios where health shocks do or do not occur at different points in the life cycle for individuals with differing endowments. Moreover, a policy simulation investigates minimum pension benefits as an insurance against old age poverty. While such a reform raises a concern about an increase in abuse of the early retirement option, the simulations indicate that a means test mitigates the moral hazard problem substantially.
Keywords: C61; I14; J22; J26; 330; dynamic programming; discrete choice; health; employment; early retirement; consumption; tax and transfer system